The Research on Real-Time Collision Detection of Large-Scale Complex Dynamic Scene - Zhang, Ying; Zhao, Wei (Applied Mechanics and Materials, 2013)
The rapid real-time collision detection is one of technical difficulties in large-scale simulation of complex dynamic scenes. Complex large-scale real-time scenario, demands of users on the efficiency and the accuracy of collision detection is higher and higher, which has made it become the subject of people to study. Based on the domestic and foreign existing collision detection algorithm, improved the process of collision detection framework, designed and implemented parallel collision detection with method of SIMD technology and multithreading programming, and made combination of these used in the collision detection of complex and dynamic scenes. Experimental results show that the algorithm design made the object in large and complex space of the 3D scene could be achieved real-time simulation. And the method solved the graphic images of moving objects and undetected penetration phenomena, shorten the detection time and response time of the collision for deformation object, increased the realism and immersion.